EFEKTIVITAS PENGGUNAAN ALAT PERAGA TERHADAP HASIL BELAJAR KIMIA DAN FISIKA PADA SISWA KELAS IX SMP SATU ATAP WASUR MERAUKE - Henie Poerwandar Asmaningrum (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2017)
Abstract. SMP Satu Atap Wasur is a boarding school located 49 km from the administrative center of Merauke regency. The school is also in protected Wasur National Park area. The student mostlyare indigenous’s Papua that residing around Wasur National Park. The inadequacy of school facilities is a challenge for chemistry and physics teachers in explaining abstract material. The existence of visual aids from Musamus University by program KKN PPM is very helpful for teacher in teaching and learning process. The purpose of this study is to know the effectiveness of using visual aids to chemistry and physics achievement. This study using comparative quantitative method with paired t test using SPSS application. The result showed that tcount<ttable (-59,144 <-2,04227) for chemistry subject and tcount<ttable (-41,327 <-2,04227) for physics subject. In conclusion, the use of visual aids effectively improve the learning result of chemistry and physics in the students of Class IX SMP Satu Atap Wasur Merauke.Keywords: achievement, chemistry, physics, visual aids